2011
DOI: 10.5121/ijcsit.2011.3419
|View full text |Cite
|
Sign up to set email alerts
|

Indian Languages IR using Latent Semantic Indexing

Abstract: Abstract. Retrieving information from different languages may lead to many problems like polysemy and synonymy, which can be resolved by Latent Semantic Indexing (LSI) techniques. This paper uses the Singular Value Decomposition (SVD) of LSI technique to achieve effective indexing for English and Hindi languages. Parallel corpus consisting of both Hindi and English documents is created and is used for training and testing the system. Removing stop words from the documents is performed followed by stemming and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Sivakumar et al [7] developed a Hindi-English CLIR system that identifies equivalent English document for the given Hindi document based on cosine similarity measure. The features of the documents to find the similarity are reduced using latent semantic indexing.…”
Section: Clirmentioning
confidence: 99%
See 1 more Smart Citation
“…Sivakumar et al [7] developed a Hindi-English CLIR system that identifies equivalent English document for the given Hindi document based on cosine similarity measure. The features of the documents to find the similarity are reduced using latent semantic indexing.…”
Section: Clirmentioning
confidence: 99%
“…It is difficult for the users *For correspondence such as farmers to pose such queries. CLIR systems [6][7][8][9][10] facilitate non-English users to pose natural language queries in their own languages but fail to handle semantics. A few research works [11][12][13][14][15] have been reported on ontology-based CLIR systems that deal with semantics using bilingual ontologies.…”
Section: Introductionmentioning
confidence: 99%
“…A concept based retrieval is known as Latent Semantic Indexing (LSI), is a method that demonstrates the singular value decomposition (SVD) [4] and vector space ranking. A.P.SivaKumar.et.al [5] proposes a combination of Latent Semantic Indexing technique with SVD to achieve efficient retrieval for Hindi and English. The limitation of the system is expensive and works only in small document collection.…”
Section: Introductionmentioning
confidence: 99%
“…A.P.SivaKumar.et.al [11] uses LSI technique with Singular Value Decomposition (SVD) to achieve effective indexing for English and Hindi languages. This paper uses the Singular Value Decomposition (SVD) of LSI technique and it solves the problem of polysemy and synonymy.…”
Section: Related Workmentioning
confidence: 99%
“…i)Assumes independence of index terms Latent Semantic Indexing i)A.P.SivaKu mar.et.al [11] ii) Neelam Phadnis and Jayant Gadge [9]s i) Retrieving text based on concept.…”
Section: International Journal Of Computer Applications (0975 -8887) mentioning
confidence: 99%